2014
DOI: 10.1002/ajpa.22630
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of skeletal treponematosis from the medieval burial ground ofSt.MarySpital,London, and implications for the origins of the disease inEurope

Abstract: Treponematosis is a syndrome of chronic infectious diseases. There has been much debate on its origins and spread, particularly with regard to venereal syphilis, an unsightly and debilitating disease in preantibiotic populations. The osteological analysis of 5,387 individuals excavated by Museum of London Archaeology from the medieval burial ground of St. Mary Spital in London (dated c 1120-1539) provided an unprecedented opportunity to investigate the nature and prevalence of disease over a period of time. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
(54 reference statements)
1
13
0
1
Order By: Relevance
“…The overall findings showed that there was a rise in treponemal infection in the late 15th century, in keeping with historical accounts at this time. However, it also indicated that evidence of treponemal disease was present in phases that dated as early as the 13th century (Walker, Powers, Connell, & Redfern, ). Such studies represent the cutting edge of what is now possible in radiocarbon dating and should provide the blueprint for future chronological analyses of treponemal disease.…”
Section: Archaeometry and Archaeological Biogeochemistrymentioning
confidence: 99%
See 3 more Smart Citations
“…The overall findings showed that there was a rise in treponemal infection in the late 15th century, in keeping with historical accounts at this time. However, it also indicated that evidence of treponemal disease was present in phases that dated as early as the 13th century (Walker, Powers, Connell, & Redfern, ). Such studies represent the cutting edge of what is now possible in radiocarbon dating and should provide the blueprint for future chronological analyses of treponemal disease.…”
Section: Archaeometry and Archaeological Biogeochemistrymentioning
confidence: 99%
“…A few studies describe individuals with treponemal disease within the context of large skeletal samples. Walker et al (), for example, described 25 affected skeletons within a very large sample of 5,387 individuals from Medieval St. Mary Spital in London. Henneberg et al () and Henneberg & Henneberg () studied a sample of 272 ancient Greek skeletons in which they found signs possibly indicating treponemal disease in 47 skeletons, including two with dental lesions of CS.…”
Section: Paleopathologymentioning
confidence: 99%
See 2 more Smart Citations
“…Treponematosis is a chronic infectious disease caused by bacteria of the genus Treponema (de Melo et al, 2010;Walker et al, 2015), and its geographical origins have been intensely debated for nearly 500 years. All paleopathological evidence from the Old World and the New World (Brothwell, 1976;Kennedy, 1990;Pàlfi et al, 1992;Zhang, 1994;Rao et al, 1996;Mays et al, 2003;Suzuki et al, 2010) indicates that acquired syphilis did not exist prior to several hundred years ago, and that it evolved from a progenitor similar to yaws in the New World prior to being transmitted to the Old World (Harper et al, 2011).…”
Section: Introductionmentioning
confidence: 99%